KERAGAMAN GENETIK POPULASI KAYU KUKU (Pericopsis mooniana, (THWAITES)THWAITES) DI HUTAN LAMEDAI BERDASARKAN PENANDA RAPD - ILG Nurtjahjaningsih; AYPBC Widyatmoko; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2019)
Vulnerable status of kayu kuku (Pericopsis mooniana) is due to heavily wood harvesting. Aim in this study is to asses genetic diversity and structure of kayu kuku at Lamedai forest, Southeast Sulawesi using RAPD markers. Leaves samples were collected from 4 natural populations at Lamedai forest i.e. Lamedai natural reserve, Lamedai village, Balijaya and Tangketada. The 22 polymorphic loci of 5 RAPD markers were subjected to the genetic analysis, binary data were calculated by GenAlex software to obtain parameters in genetic diversity within population and analysis molecular variant (AMOVA), while PopTree software was used to construct a dendrogram. Results showed that genetic diversity of the 4 populations was in moderate level (mean He: 0.361 ± 0.017) and the values was similar each other. There was no private allele at any populations, indicating that there was no genetic specification. A dendrogram analysis showed that Lamedai natural reserve genetically closed to Tangketada population and Balijaya, while Lamedai was separated into another cluster. AMOVA analysis showed 13% genetic diversity were observed among populations. In conclution, kayu kuku at Lamedai forest might be a large and continuous population in ancient period.